in Pendampingan Orang Tua dalam Menyiapkan Menu Makanan Sehat Anak - Riwantoro, Chansy Chansafani; Wijayaningsih, Lanny (Universitas Kristen Satya Wacana Salatiga, 2024)
Parents have an important role in children's health, namely providing balanced nutrition. The realization to improve children's health through the intake given to support children's growth. The purpose of this service is to provide knowledge to parents about nutritional health through the creativity of healthy food processing for children. The techniques taken are observation interviews, community service counseling and follow-up observations. KB-TK Sang Timur Salatiga, especially the Kindergarten-A class, is the main focus to improve children's nutrition through food management creativity, namely bento. The results of this community service led to the realization of food management creativity by parents for children.